2008
DOI: 10.1212/01.wnl.0000324864.81179.6a
|View full text |Cite
|
Sign up to set email alerts
|

Physical frailty in older persons is associated with Alzheimer disease pathology

Abstract: Objective: We examined the extent to which physical frailty in older persons is associated with common age-related brain pathology, including cerebral infarcts, Lewy body pathology, and Alzheimer disease (AD) pathology. Methods:We studied brain autopsies from 165 deceased participants from the Rush Memory and Aging Project, a longitudinal clinical-pathologic study of aging. Physical frailty, based on four components, including grip strength, time to walk 8 feet, body composition, and fatigue, was assessed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
186
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(201 citation statements)
references
References 36 publications
11
186
2
2
Order By: Relevance
“…Left ventricular (LV) hypertrophy (LVH), a pathologic increase in LV mass, is associated with cerebrovascular disease,1 white matter hyperintensities,2 and cognitive decline3 in aging individuals, particularly elders with hypertension 4, 5. Increased LV mass index (LV mass/body surface area) is an imaging marker that precedes LVH6 and reflects subclinical pathologic remodeling of the ventricular wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular (LV) hypertrophy (LVH), a pathologic increase in LV mass, is associated with cerebrovascular disease,1 white matter hyperintensities,2 and cognitive decline3 in aging individuals, particularly elders with hypertension 4, 5. Increased LV mass index (LV mass/body surface area) is an imaging marker that precedes LVH6 and reflects subclinical pathologic remodeling of the ventricular wall.…”
Section: Introductionmentioning
confidence: 99%
“…Given prior research linking overt LVH to cognitive impairment3 and white matter lesions,2 we hypothesized that higher LV mass index would correlate with compromised white matter microstructure on DTI and worse neuropsychological performance (especially memory) 10. Secondarily, we tested whether associations differed by cognitive diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis, therefore, used all four waves of the Canberra Longitudinal Study spanning 12 years, examined a broader range of cognitive measures that were not investigated in that earlier study individually, and adjusted for potential neuropathology over the entire 12-year period. We also investigated grip strength because decreased grip strength has been identified as a strong predictor of cognitive aging (14,15) and is associated with Alzheimer pathology and disease progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have reported that physical frailty is associated with low cognitive performance (Gill et al 1996;Strawbridge et al 1998, Avila-Funes et al 2009), incidence of Alzheimer's disease (AD; Buchman et al 2007), and mild cognitive impairment (Boyle et al 2010) and AD pathology in older persons with and without dementia (Buchman et al 2008). At present, there is no population-based study in which frailty syndrome has been investigated as possible determinant of short-and long-term all-cause mortality in demented patients.…”
Section: Introductionmentioning
confidence: 99%